A dataset of consumer perceptions of gustometer-controlled stimuli measured with three temporal sensory evaluation methods - Noëlle Béno; Léna Nicolle; Michel Visalli (Data in Brief, 2023)
This paper describes data on the consumer sensory perception of liquid mixtures including sapid and aromatic compounds. A total of 149 consumers participated in this study. They were randomly assigned to one of three panels. Each panel used a different temporal sensory evaluation method among Temporal Dominance of Sensation (TDS, n = 50), Temporal Check-All-That-Apply (TCATA, n = 50) and Attack-Evolution-Finish Rate-All-That-Apply (AEF-RATA, n = 49) to evaluate solutions delivered by a gustometer (Burghart GU002). First, four simple solutions (composed of a single compound) were delivered to the consumers to evaluate their recognition ability using Free Comment. Second, eighteen complex solutions (composed of two to five compounds varying in their sequence, intensity and duration of stimulation) were delivered to the consumers to evaluate their ability to use the three temporal evaluation methods. The compounds included sodium chloride (“salty”), saccharose (“sweet”), citric acid (“acid”), citral (“lemon”) and basil hydrosol (“basil”). The data were used to assess the validity and reliability of the temporal sensory methods in an article entitled “Assessment of the validity and reliability of temporal sensory evaluation methods used with consumers on controlled stimuli delivered by a gustometer''. The data could be reused by researchers interested in studying the effect of interactions between sapid and aromatic compounds on perception.